Kepemimpinan Kepala Sekolah dan Prfoesionalisme Guru dalam Meningkatkan Prestasi Belajar Siswa di Madrasah Tsanawiyah Swasta Minhajul Ulum Kecamatan Pujut Kabupaten Lombok Tengah - Lalu Muh Hatim Mashuri; Dwi Wahyudiati (MANAZHIM, 2023)
This study is to describe the principalof the leadership, teacher professionalism, and the principal's efforts in improving student learning outcomes at Islamic Junior High School Minhajul Ulum Pujut District Central Lombok Regency. The research method uses descriptive qualitative. The research subjects were principals, teachers and students of eight grade at Islamic Junior High School Minhajul Ulum Pujut District. Interview, observation, and documentation methods were used as data collection techniques. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results showed that (1) the leadership quality of the principal in improving teacher performance was in accordance with the research indicators, namely the principal as an innovator, supervisor, and motivator. (2) Teacher professionalism during learning is not in accordance with research indicators, namely the ability to plan, carry out learning activities, and conduct evaluations, there are still teachers who cannot control the class during learning(3) School principals' efforts to improve teacher performance by: (a) ensuring learning plans, (b) evaluation with direct monitoring, (c) developing teacher professionalism (d) quality improvement and (e) provision of wifi/internet facilities in schools. (4)The impact of the quality of the principal's leadership and teacher professionalism has a positive effect on improving the Civics learning performance of eight grade at Islamic Junior High School Minhajul Ulum Pujut District Central Lombok Regency.